Inequality Aversion, Health Inequalities, and Health Achievement - Wagstaff, Adam (World Bank, Washington, DC, 2013)
The author addresses two issues. First, how can health inequalities be measured so as to take into account policymakers' attitudes toward inequality? The Gini coefficient and the related concentration index embody one particular set of value judgments. Generalizing these indexes allows alternative sets of value judgments to be reflected. And second, how can information on health inequality be combined with information on the mean of the relevant distribution to obtain an overall measure of health "achievement?" Applying the approach developed by Wagstaff shows how much worse some countries perform when the focus switches from average health to an achievement index that also reflects the health gap between the poor and the better-off.